Impact of frozen storage on whole wheat starch and its A-Type and B-Type granules isolated from frozen dough. (1st November 2019) - Yang, Zixuan; Yu, Wenjie; Xu, Dan; Guo, Lunan; Wu, Fengfeng; Xu, Xueming
Highlights: B-Type granules were more sensitive to freezing than A-Type granules. The properties of whole wheat starch were close to those of its A-Type granules. A-Type granule gradually play a leading role in whole wheat starch with frozen time. The deterioration of B-Type granule had little influence in whole wheat starch. Abstract: The physicochemical properties of whole wheat starch and its A-Type and B-Type granules isolated from frozen dough at 0, 4 and 8 weeks of storage were investigated. Results showed that profiles of A-Type granules were more or less constant while significant differences of B-Type granules involving in irregular edges, increased relative crystallinities and decreased Viscosities were observed after 8 weeks of storage, suggesting that B-Type granules were more sensitive to freezing. These were mainly attributed to the release of leaching materials from starches, resulting in the ratio of amylose to amylopectin, protein and lipid content decreased by 25.93%, 12.05% and 31.65%, respectively. Whole wheat starch remained essentially unchanged during freezing. It seemed that B-Type granules, as a small part of whole wheat starch, had less influence on whole wheat starch than A-type granules in spite of their significant deterioration upon storage.